Voicing the Unspeakable. Political Dissent in Three Early Modern Plays - Sebellin, Rossana (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2023)
This paper explores how the lower classes voice discontent or political dissent in an acceptable balance between insubordination and formal respect of authority in three early modern texts written between the 1590s and the first decade of the 17th century. The plays under analysis are The Life of Jack Straw and Thomas of Woodstock (both anonymous) and Shakespeare’s Richard II, which all deal with the same sovereign and his reign, characterised by three main crises. Despite their distinct approaches, they all address political grievances and present their own interpretations of monarchy, political power and the role of kingship. The comparison shows interesting shifts in the vision of the commonwealth and in the perception of power in a clear progression towards radicalisation in the criticism of the king, which leads to the later Civil War.